Disposition of KW-4679(4): Metabolism of KW-4679 in Rats and Dogs - YASUZAWA, Tohru; OHISHI, Takayoshi; MAGARA, Hiroshi; YAMAGUCHI, Kazuo; KOBAYASHI, Hiroyuki; KOBAYASHI, Satoshi (Drug Metabolism and Pharmacokinetics, 1995)
The metabolism of KW-4679 was investigated in rats and dogs after oral administration of 14C-KW-4679 or KW-4679. 1) After oral administration to rats, N-mono-demethyl-KW-4679 (Ml), N-di-demethyl-KW-4679 (M2), KW-4679 N-oxide (M3), C8-hydroxyl-KW-4679 (M5), M5 sulfate (M4) and oxidated M5 (M6) were identified as the metabolites of KW-4679 in bile in addition to unchanged KW-4679. 2) When 14C-KW-4679 was orally administered to fasting male rats, 66.4% of radioactivity detected in plasma at 0.5 hr after administration, accounted for the unchanged KW-4679. The main metabolite in plasma was M1 (7.7%). In urine, also, radioactivity was present mainly as the unchanged KW-4679, which represented 27.3% of dose. The main metabolite excreted in urine was M1 (6.0%) followed by M6, M5, M2, M3 and then by M4. The main metabolite in bile was M6 followed by M4 and then by the unchanged KW-4679. In feces, 19.4% of administered radioactivity was excreted as the unchanged KW-4679. The main metabolite in feces was M5 (5.1%) followed by M6, M1, M4, M2 and then by M3. 3) After oral administration to fasting female rats, the unchanged KW-4679 was a main component of radioactivity excreted in urine, same as in male rats. 4) When 14C-KW-4679 was orally administered to fasting male dogs, 71.1% of radioactivity detected in plasma at 0.5 hr after administration was the unchanged KW-4679. The main metabolite in plasma was M3 (11.0%). The major component in urine was the unchanged KW-4679 (51.6%) followed by M1 (4.5%), M3, M5, M2, M6 and then by M4. KW-4679 was the major component excreted also in feces, representing 6.0% of dose followed by M5, Ml, M6, M4 and then by M2. 5) The metabolic pathway of KW-4679 in rats and dogs consisted of oxidative N-demethylation of the side chain and hydroxylation of dibenzoxepine ring and its sulfation and further oxidation of N-atom in the side chain.